2017
DOI: 10.1038/s41598-017-10890-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bioactive Amino Acids from Fish Hydrolysates with a New Bioinformatic Intelligent System Approach

Abstract: The current economics of the fish protein industry demand rapid, accurate and expressive prediction algorithms at every step of protein production especially with the challenge of global climate change. This help to predict and analyze functional and nutritional quality then consequently control food allergies in hyper allergic patients. As, it is quite expensive and time-consuming to know these concentrations by the lab experimental tests, especially to conduct large-scale projects. Therefore, this paper intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…ACE inhibition activity varied between different samples as it is affected directly by chemical composition and structure [6]. Noteworthy, recent studies support our results and reported that temperature has the greatest effect on protein metabolism and gene expression of amino acids in fish [1,31].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…ACE inhibition activity varied between different samples as it is affected directly by chemical composition and structure [6]. Noteworthy, recent studies support our results and reported that temperature has the greatest effect on protein metabolism and gene expression of amino acids in fish [1,31].…”
Section: Resultssupporting
confidence: 78%
“…Functional properties of peptides with antihypertensive effect are directly related to their chemical structure [1]. Therefore, the structure-function relationship of peptides from protein hydrolysates needs to be analyzed in depth to allow optimal use of their chemical diversity by the chemical industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is of especial interest in the industrial starch fermentation for the production of alcohols, amino acids, high-glucose and high-maltose syrups, which relies on pullulanase to degrade a-1,6-glycosidic linkages to improve starch hydrolysis [102]. Elaziz et al [103] also used bioinformatics to generate a prediction algorithm to enhance the properties of fish products with therapeutic and industrial roles, bioactive amino acids. Using biotechnological approaches, the concentration level of these compounds was assessed in protein hydrolyzates extracted from tilapia fish.…”
Section: Bioinformatics In the Food Industrymentioning
confidence: 99%
“…Therefore, the use of these in silico tools avoids the expense of laboratory time and reagent money. Additionally, they have allowed to find new BP from alternative sources, e.g., kefir milk ( Amorim et al, 2019a ), collagen ( Nuñez, Guzmán, Valencia, Almonacid & Cárdenas, 2020 ), fish skin ( Elaziz, Hemdan, Hassanien, Oliva & Xiong, 2017 ), invasive sea grass Halophila stipulacea ( Kandemir-Cavas, Pérez-Sánchez, Mert-Ozupek & Cavas, 2019 ), Chlorella sorokiniana ( Tejano, Peralta, Yap, Panjaitan & Chang, 2019 ), cyanobacterium Arthrospira platensis ( Ji et al, 2018 ), among many others.…”
Section: Introductionmentioning
confidence: 99%